Psychological pathways to perceived employability: a dual-theoretical lens on the mediating roles of self-efficacy and resilience in career development programs - Salisu, Isyaku; Alshammari, Mohammad Mulayh; Al-Samhi, Nezar Mohammed (Frontiers in Education, 2026)
IntroductionUnder current labor market uncertainties, employability has been an increasing concern for higher education students. As such, perceived employability is gaining importance and becoming a significant field of inquiry. However, how it is influenced in the academic environment remains inadequately studied. Drawing from the dual theoretical lens of social cognitive career theory and conservation of resources theory, this study investigates the impact of career development programs (CDP)—mentoring, training, and internships—on perceived employability, mediated by self-efficacy and resilience, among final-year university computer science students in the Hail area of Saudi Arabia.MethodsIn this cross-sectional study, data were collected from 348 university graduating computer science students. This study used partial least squares structural equation modelling to assess the measurement and structural model.ResultsMentoring and training were significantly related to perceived employability, while internships were not. For predictors of self-efficacy, only internships predicted employability, while mentoring and training did not. Self-efficacy did not predict perceived employability. Mentoring, training, and internships were significantly related to resilience. Resilience and perceived employability were significantly related. Self-efficacy mediated the relationship between internship and perceived employability but did not mediate the relationship between mentoring and training and perceived employability. Resilience mediated the relationship between mentoring, training, and internship, and perceived employability.DiscussionThe findings of this study contribute to the literature on CDPs and perceived employability and provide valuable insights for policymakers, career development program developers, and educators. By emphasizing the importance of key career development program functions, educational institutions can develop effective programs and interventions that bridge the skill gap and enhance computer students’ career prospects and employability.